2018
DOI: 10.3390/ijms19040989
|View full text |Cite
|
Sign up to set email alerts
|

The Horizon of a Therapy for Rare Genetic Diseases: A “Druggable” Future for Fibrodysplasia Ossificans Progressiva

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic condition characterized by progressive extra-skeletal ossification leading to cumulative and severe disability. FOP has an extremely variable and episodic course and can be induced by trauma, infections, iatrogenic harms, immunization or can occur in an unpredictable way, without any recognizable trigger. The causative gene is ACVR1, encoding the Alk-2 type I receptor for bone morphogenetic proteins (BMPs). The signaling is initiated by BMP binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 85 publications
0
30
0
1
Order By: Relevance
“…N-(4-Methoxyphenyl)-4-(1-propan-2-yl-3-pyridin-3-ylpyrazol-4-yl) 4-(1-Ethyl-3-pyridin-3-ylpyrazol-4-yl)-N-(4-piperidin-4ylphenyl)pyrimidin-2-amine (18f) The title compound 18f was prepared from compound 17 and tert-butyl 4-(4-aminophenyl)-1-piperidinecarboxylate following a procedure similar to that used to prepare compound 18e. 1 Expression and Purification of ALK2 (R206H) The ALK2 kinase domain including residues 201 to 499 with the R206H mutation was expressed with a recombinant baculovi-rus expression system. Sf9 cells were inoculated at 27°C and harvested 48 h after infection.…”
Section: -{4-[2-(4-methoxyanilino)pyrimidin-4-yl]-3-pyridin-3ylpyrazmentioning
confidence: 99%
See 2 more Smart Citations
“…N-(4-Methoxyphenyl)-4-(1-propan-2-yl-3-pyridin-3-ylpyrazol-4-yl) 4-(1-Ethyl-3-pyridin-3-ylpyrazol-4-yl)-N-(4-piperidin-4ylphenyl)pyrimidin-2-amine (18f) The title compound 18f was prepared from compound 17 and tert-butyl 4-(4-aminophenyl)-1-piperidinecarboxylate following a procedure similar to that used to prepare compound 18e. 1 Expression and Purification of ALK2 (R206H) The ALK2 kinase domain including residues 201 to 499 with the R206H mutation was expressed with a recombinant baculovi-rus expression system. Sf9 cells were inoculated at 27°C and harvested 48 h after infection.…”
Section: -{4-[2-(4-methoxyanilino)pyrimidin-4-yl]-3-pyridin-3ylpyrazmentioning
confidence: 99%
“…Fibrodysplasia ossificans progressiva (FOP) is a rare disorder that shows progressive heterotopic ossification in the muscles, tendons, or ligaments with an incidence of 1 in 2 million individuals. 1,2) FOP is caused by abnormal activation of bone morphogenetic protein (BMP) signaling due to highly recurrent mutations, including R206H in activin receptor-like kinase-2 (ALK2) (encoded by ACVR1 gene), a subtype of BMP type-I receptors, resulting in an alteration in the intracellular glycine-serine-rich domain of the enzyme. Diffuse intrinsic pontine glioma (DIPG), a fatal brain cancer that forms in the brainstem of children, is another disease caused by the R206H mutation of ALK2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the breakthrough discovery of the genetic basis of FOP, research trials have begun targeting various potential aspects and areas of the BMP signalling pathway, and various cell models are being prepared. The current research strategies are targeting dysregulated BMP signalling with agents like Dorsomorphin, Perhexiline and Imatinib mesylate; neofunction of the mutated ACVR1 receptor with anti-ActA antibodies and Rapamycin; the chondrogenetic differentiation processes with retinoic acid receptor gamma agonists like Palovarotene; the expression of the mutated receptor; the immune system with corticosteroids; as well as the local microenvironment of the lesions [ 17 - 19 ]. Although there has been significant progress in basic and translational research in FOP in the recent past, a lot of knowledge is yet to be unearthed.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between retinoid signalling and chondrogenesis is antagonistic: several elegant studies have shown that skeletal precursor cells treated with at RA, and with subsequent activation of retinoid signalling, have repressed chondrogenesis and cartilage formation . By allowing chondrogenesis to proceed only in the absence of retinoid signalling, this mechanism helps keep mesenchymal condensations in their prechondrogenic state and blocks differentiation into chondroblasts .…”
Section: Palovarotenementioning
confidence: 99%